Beyond Boundaries: Nurturing Diversity in Higher Education Leadership-Insights from Women’s Journeys in Pakistan - Raja, Bushra Inayat (Annals of Human and Social Sciences, 2024)
This study challenges the notion of gender-specific leadership, contributing to the global discourse on women's advancement in higher education management within the context of Pakistani universities. Using qualitative methods, the research engages in in-depth interviews and focused group discussions with 48 women in junior and senior management roles, offering a nuanced understanding of factors influencing their career progression. It emphasizes that gender should not dictate capabilities or leadership aptitude, advocating for a more inclusive approach to career development in higher education. The findings underscore that women's success in senior leadership involves a blend of personal and professional qualities, adding depth to existing literature on women in academic leadership. Addressing the need for societal attitude and cultural prejudice change, the study highlights the necessity for legislative measures and societal shifts to attain equity in top managerial positions for women. The study's implications extend to future research, providing insights into potential directions for examining factors influencing women's advancement to top management roles.